Casinga-cheirosa organic extract impairment over Balb-c male mice behavioral phenotype - Estork, Dirce M. [UNESP]; Gusmao, Daniela F. [UNESP]; Paciencia, Mateus L. B. [UNESP]; Frana, Sergio A. [UNESP]; Diaz, Ingrit E. C. [UNESP]; Varella, Antonio D. [UNESP]; Younes, Riad N. [UNESP]; Reis, Luiz F. L.; Montero, Edna F. S.; Bernardi, Maria M. [UNESP]; Suffredini, Ivana B. [UNESP] (Soc Brasileira Farmacognosia, 2016)
Laetia suaveolens (Poepp.) Benth., Salicaceae, popularly known as casinga-cheirosa, caferana, or laranjinha, is native to Brazil but not endemic to this country. A crude organic extract was obtained from the leaves and stem and intraperitoneally administered in male Balb-c mice. Its behavioral effects were evaluated in the open field and elevated plus maze in a two-stage experiment that assessed ten different parameters related to behavior as locomotion, emotionality, and anxiety. In the first stage of the experiment, intraperitoneal the crude organic extract administration dose-dependently impaired locomotion and emotionality 30-120 min after administration. A significant decrease in defecation was observed, which was related to emotionality. No alterations in the elevated plus maze were found; thus, this apparatus was not used in the next stage of the experiment. In the second stage, the previously determined non-lethal dose of 0.1563 g/kg was intraperitoneally administered, which impaired locomotion and rearing frequency and increased immobility time. Necropsy revealed smooth intestine hemorrhage. Rutin, leucoside, nicotiflorin, guaijaverin, and astragalin were isolated from the crude organic extract. This is the first time that these compounds have been identified in L. suaveolens. In conclusion, the crude organic extract impaired locomotion and emotionality and caused hemorrhage in male Balb-c mice, indicating that its consumption can be harmful to humans and animals. The present results provide a basis for further studies on the pharmacology, toxicology, and natural product chemistry of the crude organic extract. (C) 2015 Sociedade Brasileira de Farmacognosia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Laetia suaveolens; Salicaceae; Open field; Elevated-plus maze; Locomotion; Emotionality